Solitary fibrous tumor of the kidney - KAYA, HANDAN; BOZKURT, SÜHEYLA (WILEY, 2007)
Solitary fibrous tumors are rare spindle cell neoplasms usually arising in the pleura. They have, however, also been reported at extrapleural locations. Solitary fibrous tumor (SFT) of the kidney is rare. Despite its rarity, histological diagnosis of solitary fibrous tumor is crucial to avoid misdiagnosis with other more aggressive tumors arising in the kidney. We report a solitary fibrous tumor of the left kidney that presented as a malignant tumor in a 51-year-old woman, and include clinical and radiographic findings. The tumor was well circumscribed and composed of spindle cells in a collagenous stroma. Immunohistochemistry showed reactivity for vimentin, CD 34, BCL-2 protein and CD99. Immunohistochemical stains for cytokeratin, S-100, desmin, alpha-smooth muscle actin and HMB-45 were negative. A diagnosis of SFT was made based on light microscopy and immunohistochemistry.
Keywords: solitary fibrous tumor; CD 34; BCL-2; CD99; kidney; SPECTRUM; BENIGN